On the causal links between poverty and HIV in Nigeria, 1990-2009: An application of Granger causality and co-integration techniques - ﻿Halima Salihi Ahmad,; ﻿Madeline Berma,; ﻿Norlaila Abu Bakar, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
﻿The increasing rates of HIV/AIDS epidemics in Nigeria are posing serious challenges to the individuals, community, government and international donor agencies and raise critical questions as to whether poverty is a significant contributor to the growth of the disease. This paper utilises the Granger Causality Test to investigate the causative relationship between poverty and HIV in Nigeria. The results indicate no direct and significant linkages between poverty and HIV, meaning that poverty is not the driving force behind the increased rates of HIV prevalence in the country. Conversely, HIV was found to have caused increased rates of poverty in the country. In the light of these findings it is suggested that policies that would improve health and education should be implemented, together with the awareness enhancement of the public on the imperative of HIV screening prior to marriage contracts.